Laparoscopic Herniotomy for congenital inguinal hernia: prospective assessment of feasibility and outcome analysis in tertiary center in Nepal - Shrestha, Ritesh; Shrestha, Sudip (Journal of Society of Surgeons of Nepal, 2018)
Introduction: Congenital Inguinal hernia (CIH) repair is frequently performed surgical procedures in children. Open herniotomy is standard treatment for CIH. However, in developed countries laparoscopic repair is gaining popularity. The benefits of laparoscopic hernia repair are its safety, cosmetic results, opportunity to repair contralateral patent processus vaginalis (CPPV). The aim of this study was to assess feasibility and outcome of Laparoscopic herniotomy (LH) in tertiary center in Nepal. Methods: This is prospective observational study conducted at Nepal Medical College Teaching Hospital, Pediatric Surgery Unit from 1st November 2015 to 30th October 2016. All children of age greater than six months with CIH were included in this study after consent from parents. Demographic profile, operative findings, postoperative results, complications and recurrences were recorded. Results: We had 60 children, 45 males and 15 females who underwent laparoscopic herniotomy. 33 of them had right, 24 had left and 3 had bilateral hernias. The mean operating time was 30.12 minutes and 35 minutes for unilateral and bilateral hernias respectively. 14 were associated with CPPV and were repaired in same setting. We had one recurrence on right side and were repaired with open herniotomy. Conclusion: Laparoscopic herniotomy is feasible and safe in CIH. It provides better opportunity to diagnose CPPV and repair it. LH has got minimal complication and better cosmetic outcome. Larger studies and longer follow ups are needed to support our results.